Uji teknologi inokulum fungi ektomikoriza dan penambahan asam oksalat untuk meningkatkan pertumbuhan Hopea mengarawan - Melya Riniarti (Institut Pertanian Bogor, 2009)
Application of ectomycorrhizal fungi on forestry depend on some factors. Inokulum technology is one of the important factor. The aim of this research are to compare the affectivity of two inoculums from two Scleroderma spp., and to find the effect of oxalate acid on ectomycorrhizal colonization. Using cluster randomized design with ectomycorrhiza as the cluster (S. columnare and S. dictyosporum); inoculums (granular and tablet) and oxalate acid (1 times a week; 2 times a month; 4 times a month and none) as the factors. Result showed that granular inokulum can enhance the growth of Hopea mengarawan better than tablet inokulum. Oxalate acid can enhance colonization up to 8 fold.